A novel and uniform image partitioning on spiral architecture. (5th June 2006) - Wu, Qiang; He, Xiangjian; Hintz, Tom; Ye, Yuhuang
Uniform image partitioning based on spiral architecture plays an important role in parallel image processing in many aspects such as uniform data partitioning, load balancing, zero data exchange between the processing nodes et al. However, when the number of partitions is not the power of seven like 7, 49, every sub-image except one is split into a few fragments which are mixed together. We could not tell which fragments belong to which subimage. It is an unacceptable flaw to parallel image processing. This paper proposes a method to resolve the problem mentioned above. From the experimental results, it is shown that the proposed method correctly identifies the fragments belonging to the same subimage and successfully collects them together to be a complete subimage. Then, these subimages can be distributed into the different processing nodes for further processing.